IMPLEMENTING JAS (NATURAL SURROUNDING EXPLORATION) BASED PLANT DETERMINATION PRATICUM MODEL AT KELIMUTU NATIONAL PARK - Jumilah Gago; Veronika P. Sinta Mbia Wae (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to implement models and learning tools based on an integrated JAS (Natural Surrounding Exploration) approach in the plant taxonomy course, particularly on plant determination material. This research was conducted by utilizing a descriptive method with a qualitative approach. The research was carried out from September to November 2019 in the odd semester of the 2019/2020 academic year. The samples were chosen using a purposive sampling technique. The samples consisted of 43 students from the Biology Education Study Program at Universitas Flores who took the plant taxonomy course. The research was conducted at Kelimutu National Park. Based on the results, the use of a taxonomic learning model based on natural surrounding exploration was considered quite interesting and encouraged meaningful teaching and learning activities. In addition, based on the results of interviews with biology students, this method provided several advantages, including (1) being able to increase students’ understanding of plant identification, (2) serving as an attractive medium to trigger learning motivation because it was related to the real context around it, and (3) instilling a caring attitude and love for the surrounding natural wealth and local culture.